PENERAPAN PENDEKATAN PEMBELAJARAN SAINTIFIK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN PRESTASI BELAJAR SISWA (Studi Pada Muatan Pelajaran IPA Kelas IV SD Negeri 1 Pagaralam) - Mira Pebriani (DIADIK, 2021)
This study aims to describe the application of saintific learning approach to improve critical thinking skills and student achievement in science subject content for grade IV SD Negeri 01 Pagaralam. The research design used was classroom action research and quasi-experimental. The research subjects were students of grade IV.a even semester of the 2020/2021 school year SD Negeri 01 Pagaralam. The quasi-experimental sample is class IV.b and IV.c. The research instrument used observation sheets and tests. The research data were analyzed using descriptive statistics, mean, percentage, and t-test. The results showed that the application of scientific learning approach can improve critical thinking skills and learning achievement of fourth grade students of SD Negeri 01 Pagalam Kota Pagaralam